ESTIMASI HERITABILITAS PRODUKSI SUSU SAPI PERAHFRIESIAN HOLSTEIN DI UNIT PELAKSANA TEKNIS DAERAH BALAI PENGEMBANGAN TERNAK SAPI PERAH DAN HIJAUAN MAKANAN TERNAK CIKOLE LEMBANG KABUPATEN BANDUNG BARAT PROVINSI JAWA BARAT - , ROBEN SAOSA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Friesian Holstein isone of the famous dairy cattle breed in Indonesia which has a strong structure and producing milk with high production levels. Therefore, necessary to be developed, conserved and enhanced through improved the genetic quality selection. Preparation of the breeding program required genetic information of herd such as heritability. The purpose of this researchwasto estimate the heritability of milk productionof dairy cattle herd at Technical Executor Official Unit Area Animal Cultivation Dairy Cows and Forage Pasture Cikole Lembang West Bandung Regency West Java Province. Two methods of analyses werenamely paternal half sib correlations and dam offspring regression were used as a tool to calculate the heritability. The data used properties of cow milk production were maintained in 2006 to 2012 and total used 81 different calf data lactation of 81 dam which inseminated by 9 selection bulls. The estimation of heritability which used method paternal half sib correlations was 0,39ôµ0,19 and 0,48 ôµ 0,028for heritability estimation methoddam offspring regression. The results showed that the value of heritability milk production of Friesian Holstein was highpositive category. Inconclusion, the heritability estimation many can be used as criteria nature of milk production. Keywords : Holstein Friesian, Dairy, Heritability, Milk Production, Technical Executor Official Unit Area Animal Cultivation Dairy Cows and Forage Pasture Cikole Lembang